Revitalisasi dan penerapan manajamen persediaan pada Warung Sembako Yoga Kelurahan Penatih Kota Denpasar - Sumartana, I Made; Adrie, Adrie (Penamas: Journal of Community Service, 2022)
Small and Micro Enterprises (SMEs) are business units managed individually with various limitations. Warung Yoga is one of the stalls that sell different types of vegetables, necessities and other kitchen ingredients. The problems faced include the procurement of merchandise has not paid attention to the inventory, the placement of goods is irregular, untidy, has not utilized the remaining merchandise. The solution offered to partners in the procurement of merchandise inventory should apply the model Safety Stock, Reorder Point, Economic Order Quantity, and First In First Out so that merchandise inventory can be controlled so that there is no buildup of merchandise inventory. Marketing uses social media via the web, Instagram, and Facebook in marketing merchandise. Given the limited time of the partnership program, partners must be independent. For the partnership program to run independently, partners participate, starting from providing training facilities providing training materials.